Purification of two spectrin-binding proteins: biochemical and electron microscopic evidence for site-specific reassociation between spectrin and bands 2.1 and 4.1. - Tyler, J M (1979)
Two peripheral proteins of the human erythrocyte membrane that are capable of forming a stable complex with spectrin have been purified. The proteins, band 2.1 (Mr 210,000) and band 4.1 (Mr 82,000), are water soluble and exist as monomers in solution. Both exhibit strong, specific binding to purified spectrin molecules as determined by cosedimentation in sucrose gradients and both enhance binding to spectrin-depleted, inside-out vesicles that have been stripped of bands 2.1 and 4.1. Rotary replicas of bound material reveal site-specific associations among native, but not heat-denatured, molecules.